Starożytny akt kobiecy i jego późniejsze implikacje. Uwagi na marginesie Afrodyty Knidyjskiej - Bugaj, Ewa (Poznańskie Towarzystwo Przyjaciół Nauk, 2017)
This paper investigates the female nude in ancient Greek monumental sculpture based on the Aphrodite of Knidos. It first emphasises that Greek statues mostly represent deities and heroic figures in human forms. One of the reasons for this was the anthropomorphisation of the gods and heroes, the base of the Greek religion. As a result, the image of the human body constantly occupied the imagination of sculptors. Recently, there has been a shift of interest in the study of Greek statues, particularly cult statues. Iconographic and iconological considerations have been increasingly replaced by attempts to comprehend and receive the sculpture just like ancient Greeks. The text quotes a large group of researchers who have undertaken fresh efforts to interpret Greek cult statues, combining a meticulous analysis of ancient texts with studies on the preserved body of works and the contemporary reflection on the broadly understood visual culture and the ways it influences and is received by people. Important in these studies is also the recognition of the enormous impact of the modern, especially post-Enlightenment tradition, on the contemporary reception and meaning attributed to the ancient Greek art, especially statues. The article then provides a clear overview of various interpretations of the Aphrodite of Knidos, a famous work of Praxiteles, in the context of the considerations about the statues and their agency, and explores the reflection on the development of the so-called naturalistic style in Greek sculpture. The paper shows how common is the interest in goddess-related issues, notably the one depicted in the statue from Knidos. On the one hand, this stems from the popularity of gender studies, blossoming also in antiquity research, and on the other hand, from a reflection on modern European art coming from feminist art history. Unfortunately, within these approaches, the Praxiteles’ work is subject to accusations, because the sculptor supposedly showed the weakness of Aphrodite, embarrassed with her nudity, as opposed to the proudly presented nudity in male statues. The embarrassment, covering up, shows the goddess as weak and vulnerable, susceptible to injury. The naked Aphrodite of Knidos is therefore believed to have been sexually objectified by being subordinated to the male gaze. This makes the cult statue a thing subordinated to male needs and devoid of any impact. Ewa Bugaj argues that such interpretations significantly reduce the phenomenon of the cult statues and its functioning in antiquity, as presented at the beginning of the paper. We cannot forget that Aphrodite was first of all the goddess, not an ordinary woman, and the religious aspect of the functioning of the statue, so important for the ancients, should not be overlooked in the interpretation. The paper thus shows that an ancient Greek, a follower of the goddess, is unlikely to have separated his gaze from his or her religious beliefs, given that the Greeks viewed the sculpture as a statue and the goddess at the same time. Other interpretations of Praxiteles’ work are also given. It has been argued that based on religion studies as well as literary and historical references, Aphrodite cannot be called a modest goddess. Hence, her perfect and attractive body, carved by Praxiteles, was probably meant to emphasise her power. Furthermore, the decision to leave the genitals at the statue of Aphrodite of Knidos unmarked could have resulted from an intention to distinguish her divine body from the bodies of ordinary women. This permitted the goddess, embodied in the statue, to retain the status of impact and power. The nudity of the Aphrodite of Knidos rendered by Praxiteles in a very sensual manner, seemed to manifest her bodily availability, yet ultimately, the goddess was not fully accessible (both in the myths about the goddess and the legends about the statue). The beautiful, worthy of the highest admiration and lust outside of the goddess, masterfully shown by Praxiteles, enabled the Greek to image her inner divine qualities. Thus, the aim of the representation was perhaps not to stimulate lusty glances and intimate relations with the statue, but to inspire religious awe and elation.
Ancient Female Nude and Its Subsequent Implications. Remarks in the Context of the Aphrodite of Knidos
Keywords: ancient art; ancient statue; ancient cult statue; female nude; Aphrodite of Knidos; agency in art; contemporary reception of ancient Greek art